Aquinas’s Argument for an Uncaused Cause - Lamont, John R. T. (New blackfriars, 2025)
Aquinas presents his argument for the existence of an uncaused cause of all effects in his Second Way in the Summa theologiae as a deductively valid argument from premises known with certainty. This seems unwarranted, since the argument gives no reason for there being only one uncaused cause, and the reasons it gives for rejecting an endless causal regress seem unconvincing. These apparent shortcomings can be better understood by examining Aquinas’s metaphysics of causation, which is presupposed by the argument. He uses a form of composition argument to justify the claim that endless per se causal series cannot exist. He does not argue against the possibility of a multiplicity of uncaused causes because he sees no rational grounds for entertaining this possibility. Given Aquinas’s metaphysical assumptions, it is correct to take the Second Way to be a deductively sound argument.